Organophosphate Insecticide Poisoning and Parkinsonism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
Extrapyramidal parkinsonism in a 14 year-old boy developed 5 days after the accidental ingestion of a raw eggplant sprayed with the organophosphate dimethoate (Rogor), in a report from Meyer Children Hospital, Rappaport School of Medicine, Haifa, Israel.